Micro-alloyed aluminum air battery anode suitable for inert electrolyte and preparation method of micro-alloyed aluminum air battery anode
The microalloyed aluminum-air battery anode, prepared via electromagnetic stirring and quenching, addresses discharge voltage and energy density issues, ensuring stable performance and safety in inert electrolytes.
Patent Information
- Application Number
- CN202411337789.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
Aluminum anodes in aluminum-air batteries face issues with severe polarization and low discharge voltage in inert electrolytes, and self-corrosion and hydrogen evolution in active electrolytes, leading to reduced discharge performance and safety risks.
A microalloyed aluminum-air battery anode composed of Mg, In, and Ga with high-purity aluminum, prepared through high-frequency electromagnetic stirring and two quenching steps, enhances solid solution and phase distribution, stabilizing discharge voltage and improving energy density.
The microalloyed anode achieves high utilization rate, low hydrogen evolution, and extended discharge time, making it suitable for inert electrolytes and reducing safety risks.
Smart Images

Figure CN119220834A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum-air batteries, and in particular to a microalloyed aluminum-air battery anode suitable for an inert electrolyte and a preparation method thereof. Background Art
[0002] Metal-air batteries have been regarded as the next generation of new energy to alleviate the growing demand for energy. Among them, aluminum-air batteries have attracted more and more attention compared to zinc-air batteries and magnesium-air batteries because their aluminum anodes have advantages such as higher theoretical energy density (8100Wh / kg), abundant reserves, low cost, recyclability, and environmental friendliness. However, aluminum as an anode faces many problems during discharge. In an inert electrolyte, as the discharge time increases, the protective oxide film and hydroxide film formed on the surface of the aluminum anode lead to severe anode polarization, making the actual working potential of the aluminum anode much lower than the theoretical potential, resulting in lower discharge voltage and energy density, and unable to discharge for a long time. In a highly active electrolyte, the self-corrosion of the aluminum anode is seriously aggravated due to the damage of the electrolyte to the protective film, thereby reducing the discharge performance of the aluminum anode in the electrolyte; and due to the intensification of self-corrosion hydrogen evolution, the hydrogen content in the battery increases, and the risk factor increases. Therefore, it is necessary to propose a microalloyed aluminum-air battery anode suitable for an inert electrolyte and a preparation method thereof to solve the above problems. Summary of the invention
[0003] The purpose of the present invention is to address the deficiencies of the prior art and provide a microalloyed aluminum-air battery anode suitable for an inert electrolyte and a preparation method thereof, so as to solve the problem that the aluminum anode has a low discharge operating voltage and low energy density under an inert electrolyte and cannot be discharged for a long time.
[0004] In a first aspect, the present invention provides a method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte, wherein the aluminum-air battery anode is composed of the following components in mass percentage: Mg: 0.5-2wt%, In: 0.05-0.4wt%, Ga: 0.05-0.1wt%, and the remainder is 4N high-purity aluminum; the preparation method comprises the following steps:
[0005] Step 1: According to the above mass percentage, high-purity aluminum ingots with a purity of ≥99.99%, metal magnesium with a purity of ≥99.99%, metal indium with a purity of ≥99.99%, and metal gallium with a purity of ≥99.99% are selected as raw materials, and the aluminum ingots are melted under a protective atmosphere and high-frequency electromagnetic stirring to obtain a melt;
[0006] Step 2, keeping the melt warm for 10-20 minutes, with the melt temperature at 730-740° C., and preparing an aluminum alloy ingot through a metal mold;
[0007] Step 3, subjecting the prepared aluminum alloy ingot to a first quenching treatment under a protective atmosphere;
[0008] Step 4, subjecting the aluminum alloy ingot to a multi-pass rolling process at room temperature to obtain a rolled plate;
[0009] Step five, subjecting the rolled plate to a second quenching treatment under a protective atmosphere to obtain an aluminum-air battery anode.
[0010] Furthermore, in step one, the aluminum liquid is refined once using a refining agent with a mass ratio of 0.1 to 0.2%, and is allowed to stand for 5 to 10 minutes after refining; the secondary refining temperature is 720 to 730°C, and refining is performed after adding metallic magnesium; after refining, the temperature is lowered to 720°C, metallic indium and metallic gallium are added, and high-frequency electromagnetic stirring is performed.
[0011] Furthermore, in step 2, after the melt is kept warm for 10-20 minutes and the melt temperature is 710-720°C, the temperature is raised to 730-740°C and kept warm for 10-20 minutes, and an aluminum alloy ingot is prepared by a metal mold.
[0012] Furthermore, in step three, the first quenching temperature is 420-450° C., the holding time is 10-12 hours, and water quenching is performed immediately after the holding is completed.
[0013] Furthermore, in step 4, the rolling temperature is room temperature and the rolling deformation is 65%-75%.
[0014] Furthermore, in step five, the second quenching temperature is 200-250° C., and the insulation is performed for 1-2 hours. After the insulation is completed, water quenching is performed immediately.
[0015] In a second aspect, a microalloyed aluminum-air battery anode suitable for an inert electrolyte is provided, wherein the microalloyed aluminum-air battery anode suitable for an inert electrolyte is prepared by the above-described method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte; the microalloyed aluminum-air battery anode has a hydrogen evolution rate of ≤0.12 mL / cm under the conditions of an inert electrolyte and a temperature of 50±10°C. -2 min -1 , Anode utilization ≥ 80%, 5-40mA·cm -2 Under the above conditions, the continuous discharge time is ≥200h and the energy density is 2500-3500Wh / Kg.
[0016] In a third aspect, a microalloyed aluminum-air battery suitable for an inert electrolyte is provided, wherein the aluminum-air battery comprises the microalloyed aluminum-air battery anode suitable for an inert electrolyte as described above.
[0017] In a fourth aspect, one or more microalloyed aluminum-air battery anodes suitable for inert electrolytes are used in the field of metal fuel cells.
[0018] The present invention has the following beneficial effects: the present invention provides a microalloyed aluminum-air battery anode suitable for inert electrolyte and a preparation method thereof, through high-frequency electromagnetic stirring during melting and casting, and two quenching steps of subsequent heat treatment, the extremely easy segregation phase is dissolved back into the matrix to achieve ultra-high solid solution, the type and distribution of the precipitated phase are changed, the ultra-high activity of the anode is achieved, the discharge working voltage is stable in the inert electrolyte for a long time, and the problem of low discharge working voltage and energy density of the anode in the inert electrolyte is improved. The overall battery pack is expected to replace the current industrial high-activity electrolyte aluminum-air battery pack and reduce the risk of severe hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is a macroscopic image of the aluminum-air battery anode material suitable for inert electrolyte before and after discharge in this application example;
[0021] Figure 2 This is a microscopic schematic diagram of an aluminum-air battery anode suitable for an inert electrolyte according to an example of this application;
[0022] Figure 3 This is a schematic diagram of the microscopic precipitation phase in the anode of an aluminum-air battery suitable for an inert electrolyte in an example of this application;
[0023] Figure 4 This is a schematic diagram of the actual discharge of the aluminum-air battery anode suitable for inert electrolyte in the example of this application, wherein the cathode is a commercial nickel mesh cathode with MnO2 / C as the catalytic layer. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with the embodiments. It should be noted that the following detailed descriptions are all illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the present application belongs.
[0025] See also Figures 1 to 4The present invention provides a microalloyed aluminum-air battery anode suitable for an inert electrolyte and a preparation method thereof. The aluminum-air battery anode is composed of the following components in mass percentage: Mg: 0.5-2wt%, In: 0.05-0.4wt%, Ga: 0.05-0.1wt%, and the balance is 4N high-purity aluminum. 4N high-purity aluminum refers to high-purity aluminum with a purity of 99.99% and an extremely low impurity content. The balance is 4N high-purity aluminum, which means that in the composition of the anode material, except for other components that have been clearly listed, the remaining parts are aluminum with a purity of 99.99%.
[0026] Through high-frequency electromagnetic stirring during melting and casting, and two quenching steps in the subsequent heat treatment, the phase that is extremely easy to segregate is dissolved back into the matrix to achieve ultra-high solid solution, which changes the type and distribution of the precipitated phase, realizes ultra-high activity of the anode, and the discharge working voltage is stable for a long time in an inert electrolyte such as 0-3M NaCl, 0-2M NaOH, and 0-2M KOH, thereby improving the problems of low discharge working voltage and energy density of the anode in an inert electrolyte.
[0027] The aluminum anode prepared in this application achieves a high anode utilization rate (≥80%), and the hydrogen evolution rate is ≤0.12mLcm under the conditions of no discharge, high temperature (≥50°C) and inert electrolyte. -2 min -1 , achieving ultra-high safety; the overall battery pack is expected to replace the current industrial high-activity electrolyte aluminum-air battery pack and reduce the risks caused by severe hydrogen evolution.
[0028] The method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte according to the present invention is described below in conjunction with several specific embodiments.
[0029] Example 1
[0030] 1. The chemical composition of the aluminum-air battery anode blank suitable for inert electrolyte is as follows by mass percentage: Mg: 0.5%, In: 0.05%, Ga: 0.05%, and the rest is Al. Mg, In, Ga and Al are all added in the form of pure substances, and the burnout of Mg is calculated as 5%. The purity of the above metals is ≥99.99%.
[0031] 2. The present embodiment is applicable to the preparation method of the aluminum-air battery anode material for an inert electrolyte, comprising the following steps:
[0032] (1) Melting: Heat the aluminum ingot in a protective atmosphere until it melts. When the temperature rises to 690°C, use a refining agent with a mass ratio of 0.1-0.2% to refine the aluminum liquid. After refining, let it stand for 5-10 minutes. Then heat it to 720°C and add metal magnesium. Stir and keep warm for 10 minutes. Then heat it to 740°C for secondary refining. After refining, cool it to 720°C, add metal indium and metal gallium, and perform high-frequency electromagnetic stirring. After the electromagnetic stirring is completed, heat it to 730-740°C and pour it into a metal mold. Air cool it to room temperature and obtain the target thickness ingot after wire cutting.
[0033] (2) First quenching: The ingot obtained in (1) was placed in a homogenizing furnace and kept at 450°C for 12 h. After the end of the holding period, it was immediately water quenched.
[0034] (3) Plastic deformation process: The ingot obtained in (2) is subjected to multiple passes of room temperature rolling, and the final deformation amount is 75%.
[0035] (4) Second quenching: The rolled plate obtained in (3) is placed in a muffle furnace and kept at 250° C. for 2 h. After the end of the heat preservation, it is immediately subjected to water quenching to obtain an aluminum-air battery anode material.
[0036] Example 2
[0037] 1. The chemical composition of the aluminum-air battery anode blank suitable for inert electrolyte is as follows by mass percentage: Mg: 0.5%, In: 0.1%, Ga: 0.05%, and the rest is Al. Mg, In, Ga and Al are all added in the form of pure substances, and the burnout of Mg is calculated as 5%. The purity of the above metals is ≥99.99%.
[0038] 2. The present embodiment is applicable to the preparation method of the aluminum-air battery anode material for an inert electrolyte, comprising the following steps:
[0039] (1) Melting: Heat the aluminum ingot in a protective atmosphere until it melts. When the temperature rises to 690°C, use a refining agent with a mass ratio of 0.1-0.2% to refine the aluminum liquid. After refining, let it stand for 5-10 minutes. Then heat it to 720°C and add metal magnesium. Stir and keep warm for 10 minutes. Then heat it to 740°C for secondary refining. After refining, cool it to 720°C, add metal indium and metal gallium, and perform high-frequency electromagnetic stirring. After the electromagnetic stirring is completed, heat it to 730-740°C and pour it into a metal mold. Air cool it to room temperature and obtain the target thickness ingot after wire cutting.
[0040] (2) First quenching: The ingot obtained in (1) was placed in a homogenizing furnace and kept at 450°C for 12 h. After the end of the holding period, it was immediately water quenched.
[0041] (3) Plastic deformation process: The ingot obtained in (2) is subjected to multiple passes of room temperature rolling, and the final deformation amount is 75%.
[0042] (4) Second quenching: The rolled plate obtained in (3) is placed in a muffle furnace and kept at 250° C. for 2 h. After the end of the heat preservation, it is immediately subjected to water quenching to obtain an aluminum-air battery anode material.
[0043] Example 3
[0044] 1. The chemical composition of the aluminum-air battery anode blank suitable for inert electrolyte is as follows by mass percentage: Mg: 0.5%, In: 0.2%, Ga: 0.05%, and the rest is Al. Mg, In, Ga and Al are all added in the form of pure substances, and the burnout of Mg is calculated as 5%. The purity of the above metals is ≥99.99%.
[0045] 2. The present embodiment is applicable to the preparation method of the aluminum-air battery anode material for an inert electrolyte, comprising the following steps:
[0046] (1) Melting: Heat the aluminum ingot in a protective atmosphere until it melts. When the temperature rises to 690°C, use a refining agent with a mass ratio of 0.1-0.2% to refine the aluminum liquid. After refining, let it stand for 5-10 minutes. Then heat it to 720°C and add metal magnesium. Stir and keep warm for 10 minutes. Then heat it to 740°C for secondary refining. After refining, cool it to 720°C, add metal indium and metal gallium, and perform high-frequency electromagnetic stirring. After the electromagnetic stirring is completed, heat it to 730-740°C and pour it into a metal mold. Air cool it to room temperature and obtain the target thickness ingot after wire cutting.
[0047] (2) First quenching: The ingot obtained in (1) was placed in a homogenizing furnace and kept at 450°C for 12 h. After the end of the holding period, it was immediately water quenched.
[0048] (3) Plastic deformation process: The ingot obtained in (2) is subjected to multiple passes of room temperature rolling, and the final deformation amount is 75%.
[0049] (4) Second quenching: The rolled plate obtained in (3) is placed in a muffle furnace and kept at 250° C. for 2 h. After the end of the heat preservation, it is immediately subjected to water quenching to obtain an aluminum-air battery anode material.
[0050] Example 4
[0051] 1. The chemical composition of the aluminum-air battery anode blank suitable for inert electrolyte is as follows by mass percentage: Mg: 0.5%, In: 0.4%, Ga: 0.05%, and the rest is Al. Mg, In, Ga and Al are all added in the form of pure substances, and the burnout of Mg is calculated as 5%. The purity of the above metals is ≥99.99%.
[0052] 2. The present embodiment is applicable to the preparation method of the aluminum-air battery anode material for an inert electrolyte, comprising the following steps:
[0053] (1) Melting: Heat the aluminum ingot in a protective atmosphere until it melts. When the temperature rises to 690°C, use a refining agent with a mass ratio of 0.1-0.2% to refine the aluminum liquid. After refining, let it stand for 5-10 minutes. Then heat it to 720°C and add metal magnesium. Stir and keep warm for 10 minutes. Then heat it to 740°C for secondary refining. After refining, cool it to 720°C, add metal indium and metal gallium, and perform high-frequency electromagnetic stirring. After the electromagnetic stirring is completed, heat it to 730-740°C and pour it into a metal mold. Air cool it to room temperature and obtain the target thickness ingot after wire cutting.
[0054] (2) First quenching: The ingot obtained in (1) was placed in a homogenizing furnace and kept at 450°C for 12 h. After the end of the holding period, it was immediately water quenched.
[0055] (3) Plastic deformation process: The ingot obtained in (2) is subjected to multiple passes of room temperature rolling, and the final deformation amount is 75%.
[0056] (4) Second quenching: The rolled plate obtained in (3) is placed in a muffle furnace and kept at 250° C. for 2 h. After the end of the heat preservation, it is immediately subjected to water quenching to obtain an aluminum-air battery anode material.
[0057] The self-corrosion rates and discharge performances of the above-mentioned Examples 1-4 under inert solutions are shown in the following table:
[0058]
[0059] It can be seen from Table 1 that the self-corrosion hydrogen evolution rate of the aluminum alloy anode in Examples 1-4 of the present invention is as low as 0.075 mL·cm -2 ·min -1 -0.118mL cm -2 ·min -1 , with ultra-high safety, the air battery composed of -2 -40mA·cm -2 The lower discharge peak voltage is 1.017V-1.292V, the anode power is 2.50kWh / kg-3.45kWh / kg, and the anode utilization rate is ≥80%. The aluminum-air battery of this embodiment has a discharge time of ≥200h in the actual discharge process, a stable discharge voltage, and better discharge performance at low current density.
[0060] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte, characterized in that: The aluminum-air battery anode is composed of the following components in percentage by mass: Composition: Mg: 0.5-2wt%, In: 0.05-0.4wt%, Ga: 0.05-0.1wt%, and the balance is 4N high-purity aluminum; the preparation method comprises the following steps: Step 1: According to the above mass percentage, high-purity aluminum ingots with a purity of ≥99.99%, metal magnesium with a purity of ≥99.99%, metal indium with a purity of ≥99.99%, and metal gallium with a purity of ≥99.99% are selected as raw materials, and the aluminum ingots are melted under a protective atmosphere and high-frequency electromagnetic stirring to obtain a melt; Step 2, keeping the melt warm for 10-20 minutes, with the melt temperature at 730-740° C., and preparing an aluminum alloy ingot through a metal mold; Step 3, subjecting the prepared aluminum alloy ingot to a first quenching treatment under a protective atmosphere; Step 4, subjecting the aluminum alloy ingot to a multi-pass rolling process at room temperature to obtain a rolled plate; Step five, subjecting the rolled plate to a second quenching treatment under a protective atmosphere to obtain an aluminum-air battery anode.
2. The method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte according to claim 1, characterized in that: In step 1, the aluminum liquid is refined once using a refining agent with a mass ratio of 0.1 to 0.2%, and the aluminum liquid is allowed to stand for 5 to 10 minutes after refining; the secondary refining temperature is 720 to 730°C, and refining is performed after adding metal magnesium; after refining, the temperature is lowered to 720°C, metal indium and metal gallium are added, and high-frequency electromagnetic stirring is performed.
3. The method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte according to claim 1, characterized in that: In step 2, after the melt is kept warm for 10-20 minutes and the melt temperature is 710-720°C, the temperature is raised to 730-740°C and kept warm for 10-20 minutes, and an aluminum alloy ingot is prepared by a metal mold.
4. The method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte according to claim 1, characterized in that: In step 3, the first quenching temperature is 420-450°C, the holding time is 10-12h, and water quenching is performed immediately after the holding is completed.
5. The method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte according to claim 1, characterized in that: In step 4, the rolling temperature is room temperature and the rolling deformation is 65%-75%.
6. The method for preparing a microalloyed aluminum-air battery anode suitable for an inert electrolyte according to claim 1, characterized in that: In step 5, the second quenching temperature is 200-250°C, and the temperature is kept for 1-2 hours. After the temperature is kept, water quenching is immediately performed.
7. A microalloyed aluminum-air battery anode suitable for use in an inert electrolyte, characterized in that: The microalloyed aluminum-air battery anode suitable for inert electrolyte is prepared by the method for preparing a microalloyed aluminum-air battery anode suitable for inert electrolyte according to any one of claims 1 to 6; the microalloyed aluminum-air battery anode has a hydrogen evolution rate of ≤0.12 mL / cm under the conditions of inert electrolyte and temperature of 50±10°C. -2 min -1 , Anode utilization ≥ 80%, 5-40mA·cm -2 Under the above conditions, the continuous discharge time is ≥200h and the energy density is 2500-3500Wh / Kg.
8. A microalloyed aluminum-air battery suitable for use with an inert electrolyte, characterized in that: The aluminum-air battery comprises the microalloyed aluminum-air battery anode suitable for inert electrolyte as claimed in claim 7.
9. Use of the microalloyed aluminum-air battery anode suitable for inert electrolyte as claimed in claim 7 in the field of metal fuel cells.
